Study of the Results of Surgical and Conservative Management of Gastrointestinal Fistula - مسعود, سجيع; سعد, أحمد; حبيب, صالح (Latakia University Journal -Medical Sciences Series, 2020)
Background: Gastrointestinal fistula form a serious complication associated with high morbidity and mortality. Most gastrointestinal fistulas (85-75%) are formed as a mixture of modern surgery, and some of them occur spontaneously as manifestations of Crohn's disease or tumors. Objective: To study the results of conservative treatment and the reasons for transferring to surgical treatment, while identifying the difference between them in terms of outcomes, complications, and deaths. Materials and Methods: A review study of 56 patients at Tishreen University Hospital, Lattakia, Syria, from 2017-2019. Results: Most gastrointestinal fistulas were formed at the expense of the ileus at 44.5%. Conservative treatment was used in 39 patients who closed the fistula spontaneously in 21 patients, with a rate of 53.84%, while it was not closed in 18 patients. Transition was made to surgical treatment, 9 of whom died due to a general condition and sepsis. Direct surgical intervention was performed in 17 patients and 4 patients died. Infectious complications and electrolyte disturbances occurred at a higher rate in conservative treatment patients, and relapse occurred in two patients with conservative treatment, whereas no recurrence occurred in surgical treatment patients. Conclusion: Enterocutaneous fistulas are still a complex problem. In addition to the initial management of sepsis, conservative treatment remains the main treatment, which includes wound management, nutritional support, and psychological support. Surgical treatment should be carefully planned and left to cases where conservative treatment fails.